THE PROBLEM OF EDUCATIONAL SPREAD’S FORMATION AND DEVELOPMENT IN THE MIDDLE EAST COUNTRIES (CASE STUDY OF ISRAEL) - Dubinina, Natalia; Barabash, Victor; Ebzeeva, Julia; Gishkaeva, Luiza (PEOPLE: International Journal of Social Sciences, 2017)
The present article investigates a very specific language situation, language policy and its implementation in the educational process in Israel, that is a country in the Middle East where there is a whole palette of languages (over 32 languages) and cultures. The authors carried out a thorough analysis of the development and domination of the todays’leading languages in Israel (Hebrew, Arabic, English), dwelled upom historical factors that had influenced and shaped language dynamics in the country. The current research based on and supported by other similar reseaches in this area presents a unique case study of a dying language (Hebrew) revilatisation in the XXI c. as well as the domination of English, Arabic in the region, which in their place have pushed other existing languages (Ladino, Yiddish) to the edge of their extinction. The current research argues that such a ‘language mosaic’ is not specifically driven by any pre-planned by the state language policy, but is a reflection of extra-linguistic factors which shape the objective reality in Israel.